Does NICU Intervention Improve Survivability in Consanguineous Trisomy 13? - Hamza Ismaeel, Muhammad Nouman Rana, Armaghan Saeed, Waleed Bin Mansoor, Hamza Ismaeel, Muhammad Nouman Rana, Armaghan Saeed, Waleed Bin Mansoor (Journal of Rawalpindi Medical College, 2019)
Patau Syndrome is a fatal autosomal trisomy ,usually seen because of Meiotic nondisjunction due to maternal advanced age. It is observed at a higher frequency in non-consanguineous union.Trisomy has a prevalence of : 2,000– : 29,000 in newborns. , Also known as Patau Syndrome, it is a rare and lethal autosomal trisomy 3 with a survivability of only 7- 0 days. Only an estimated 9% to 4% of live births survive beyond year of life and are associated with mosaicism. Severity of associated malformations also plays a key role in prognosis and survival.It presents with a wide array of dysmorphic features including microphthalmia, cutis aplasia, polydactyly, cleft lip, cleft palate, various congenital heart disease, omphalocele, holoprosencephaly and urogenital abnormalities. There is an intense discussion as to whether timely NICU interventions do play a role in improving mortality in the neonate and long term better prognosis and survivability as a result , especially in VLBW(Very Low Birth Weight) infants. There is a higher reporting frequency of Trisomy’s in non-consanguineous marriages one example of which is Down Syndrome. Currently diagnosis is based on increasing maternal age, sonographic findings, serum markers and amniocentesis followed in many cases by pregnancy termination as in the West. Risk increases with increasing maternal age with an average of age of 3 years.